THE FUNCTIONALITY OF DECENTRALIZED MANAGEMENT IN THE RECONSTRUCTION OF SOCIAL SERVICES - Yusuf GENÇ (Fırat University, 2019)
The Ministry of Family and Social Policies (mülga SHÇEK) that holds an important place in carrying out the basic responsibilities of being a social state, provides daily and long-term boarding care services for the children in need of protection and care, youngsters, women, the disabled and elderly people beside protective and preventive services. In parallel with the social changes and developments in the world, recent needers and service areas emerge and therefore, it becomes indispensible to create new service models. In this context, a severe renewal is being experienced in services provided for children, women, the disabled and the poor. Services which are offered to target group’s social work, can be improved by a professional perspective and a right deployment. The protection of right to live in a healthy family environment - instead of institutional care – which accords with the human dignity is the main concern of the new service approach of the Ministry for all service users including children, the disabled and the elderly people. For this aim, families must be supported economically and psycho-socially. However, centralized management of the process can cause a variety of flaws. Decentralized management of the service offered the disadvantaged groups and the client-based practice of the applications according to the local circumstances, the served group and the related issue in the field of social work will contribute to efficiency and decrease the cost as is the case with social benefits. Social services must be conducted through a planned and programmed structure (local institutions) in which humans rights are taken into consideration, people’s voluntary contribution and participation is secured, decentralized management rules are applied and the offered service is carried out not only by central administration but also citizens. Sufficiency of programmes, creating standards and making balanced implementation throughout the country must be the main central policy. As being a theoretical study, this paper lays stress on the importance and necessity of decentralized social services.